Transmitir la corporeidad poética en el proceso de traducción. Anna Świrszczyńska traducida al español - Jackiewicz, Aleksandra (Romanica Silesiana, 2021)
The purpose of the article is to indicate the possible translation difficulties encountered by translators while recreating the corporeality represented in the poetry of Anna Świrszczyńska, considered one of the most renowned Polish poets of the twentieth century. Special attention will be paid to the poetic strategy of the author that deals with personal experiences, and whose purpose is the poetization of life through revealing the qualities of the human body. I propose to conduct a comparative study between the original poems and their Spanish translations, which aims to find out if the logical-semantic structure of the works whose main axis is the perception of corporeality has been reflected in the target texts. In addition, I try to outline in the article the extent to which its aesthetic intentionality can work in the Spanish-speaking poetic context.